Early results of a distance learning paediatric surgery programme in Mozambique - Ana Coelho; Ana Sofia Marinho; Joana Barbosa-Sequeira; André Nikutme; Leyani Noya; Carla Rêgo; Fátima Carvalho; João Moreira-Pinto (Wolters Kluwer Medknow Publications, 2022)
Introduction: A pre-graduate training programme in paediatric surgery was applied to students in four medical schools of Mozambique. In this paper, we evaluate the early results of the programme. Materials and Methods: A pre-graduate training programme was developed and applied in two stages, theoretical education available at an online platform and a face-to-face session. To evaluate the programme, a diagnostic test was applied to all participants before the face-to-face session and, the same test, was applied again at the end of the session. Results: A total of 236 students participated in the programme. Forty-four per cent had a negative score on the diagnostic test. When the test was repeated, 91.9% had a positive score, and the difference between the scores in both tests reached statistical significance (P < 0.05). The participants who completed the first phase of the programme presented a higher median score in both tests (P < 0.05). Conclusions: The diagnostic tests allowed us to verify there was an increase in knowledge before and after the face-to-face session. There was also a significant difference between those participants who completed the online phase of the programme and those who did only the face-to-face session, which allows us to conclude that the online teaching programme was effective.